Towards a particle based approach for multiscale modeling of heterogeneous catalytic reactors. (28th April 2019) - Sengar, A.; Kuipers, J.A.M.; van Santen, R.A.; Padding, J.T.
Graphical abstract: Highlights: Simulation of convection-reaction-diffusion for heterogenous catalytic reactors. Numerical computation of bulk mutual diffusivity using SRD. Incorporation of complex reaction systems while maintaining the interfacial physics. Dimensionless analysis to convey physical information between reactive systems. Different modeling examples show from linear systems to nonlinear reaction systems. Abstract: Particle based approaches are one of the recent modeling techniques to overcome the computational limitation in multiscale modeling of complex processes, for example a heterogeneous catalytic reactor. We propose an efficient model for a chemical reactor where hydrodynamics of the solvent is determined by Stochastic Rotation Dynamics and a reaction occurs over a catalytic surface where the reaction kinetics follows the mean-field assumption. We highlight the modeling techniques required to simulate such a system and then validate the model for its separate and combined components of convection, diffusion and reaction(s). A dimensionless analysis helps compare processes occurring at different scales. We determine the Reynolds number, Re, and the Damkohler numbers, Da and Da L in terms of key quantities. The approach is then used to analyse a reaction (a) following the Langmuir-Hinshelwood kinetics, (b) generating product particles with different self-diffusivity values as compared to the reactant particles. The model developed can further incorporate reactions occurring inside complex geometries (pore diffusion) and also be used to study complex reaction systems for which the mean-field assumption is no longer valid.